Effectiveness of adaptive reuse of historical building into office building / Aizuddin Masnan - Masnan, Aizuddin (2009)
Problems that usually occur at office building adapted from historical building facilities provided is related to many historical building do not have enough facilities like to require for an office, the cost in order to maintain old building is higher, the historical building usually has many problems such as facilities management and maintenance performance to ensure all the facilities provided is in a good condition. Scope of this study focused on the Klang Valley only. The study was conducted to identify the type of adaptation applied to the building of office buildings, identify common problems and factors for which they usually occur in the office building adapted from historic buildings and occupancies and the level of satisfaction to know what is the best way to overcome the problems that occurred. The study was made covering the relevant literature review followed by a circulation survey forms to the respondent to know the response of the satisfaction of building their case studies. All data that was collected has been analyzed by using manually method. The result can be known that as a whole, respondent is satisfied that the adaptation made to the building case study. However, there is also a respondent is not satisfied with the state building case study. In conclusion, this case study building to is restored using the correct methods for conservation and adaptation of this historical building. Results have been obtained can be used as a guide on public or private organizations to improve the state of historic buildings around the country where the adaptation is done with fairly standardized so there are not more common problems that occur in buildings that have been adaptation.